EFFECT OF CYCLIC MEDITATION ON CAREGIVERS STRESS AMONG FAMILIES OF CHILDREN WITH DEVELOPMENTAL DISABILITIES - Suresh, *Sudha; kumar, Vijay; Umesh, Sahana (International Journal of Ayurveda and Pharma Research, 2018)
Background and Objectives: The study explored the effect of Cyclic meditation in reduction of stress levels and enhancement of coping skills of parents of children with developmental disabilities. The research was a single group pre-post study, with convenient sampling, with a sample size of 40, all parents, primary caregivers of the children. This study used both objective and subjective measures to analyse stress and related coping skills. Methods and Materials: 40 Parents, in the age group of 30-45 years, who gave informed written consent participated in the intervention, completed the study. All participants were parents and the primary caregivers of special needs children. The variables GSR - Galvanic Skin Response, Perceived Stress and Coping in relation to Caregiving, and Social Support, were assessed using GSR sensor, CHIP and KCSS questionnaires before and after Cyclic Meditation (CM). All the participants underwent CM practices for 3 days a week for 40 minutes a day, for 8 weeks with a 2 month follow up. The parameters were repeated after 8 weeks.Results: A paired-samples t-test was conducted to compare the pre - post data, in both the objective and subjective measures, used in the study. There was a significant difference in the GSR scores for Pre-CM and Post-CM conditions; and this was significant with p = .001. The CHIP and KCSS scores did not show a statistical significance between the pre - post data. Conclusion: The study did not show a significant difference in the pre-post data of the subjective measures but there is a difference which the study failed to detect, because the study was too small, and it lacked power. However, in the objective measure of GSR to measure the stress levels, the mean GSR is significantly lower than the baseline data (p<0.05), showing that Cyclic Meditation has produced a highly significant reduction in stress levels in the participants.